IMPLEMENTASI METODE TALAQQI BERBASIS DIFERENSIASI PADA KEGIATAN BTQ DALAM MENINGKATKAN KEMAMPUAN MEMBACA AL-QUR'AN DI MI IBRAHIM ASSAMARQONDI - Lailah Tasbihah, Ahya; Ummidlatus Salamah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The ability to read the Qur’an properly is a fundamental competency for students at the madrasah ibtidaiyah level. However, differences in students’ reading abilities often pose challenges in implementing effective BTQ (Baca Tulis Al-Qur’an) learning. This study aims to describe the implementation of a differentiation-based talaqqi method in improving students’ Qur’an reading skills at MI Ibrahim Assamarqondi. This research employed a qualitative descriptive approach. Data were collected through observation, interviews, and documentation involving BTQ teachers and students. The results indicate that the implementation was conducted through several stages, namely identifying students’ initial abilities, grouping students based on their reading levels, applying direct talaqqi guidance, and conducting continuous evaluation. The findings show that this method improves students’ reading fluency, accuracy of makharijul huruf, and application of tajwid rules. Supporting factors include teacher competence, a religious school environment, parental involvement, and students’ reading habits, while the main obstacles are limited instructional time and varied student abilities. Therefore, the differentiation-based talaqqi method is considered an effective strategy to enhance students’ Qur’an reading skills.